Building New Bridges - Bâtir de nouveaux ponts Sources, Methods and Interdisciplinarity - Sources, méthodes et interdisciplinarité - Keshen, Jeff (Actexpress, 2005)
Questions of methodology and the use of sources are fundamental to all academic disciplines. In recent years, this topic has become far more challenging as scholars are increasingly adopting an interdisciplinary approach to achieve richer and deeper analyses, particularly in the humanities and social sciences. Building New Bridges / Bâtir de nouveaux ponts is a collection of scholarly papers that deals with the first principles of source identification and their effective utilization.The contributors to the volume come from a wide range of disciplines and represent both French and English Canada. Together, they explore and encourage the interdisciplinarity trend - around which considerable academic trepidation remains - and seek to explain, for example, how historians and those in English or Lettres françaises analyze texts, how scholars approach paintings, photography, and film, and how the study of music relates tempo and lyrics to wider societal trends. They utilize their respective research to elucidate means of effectively employing evidences and methods to achieve richer, deeper, and more nuanced results. As a whole, the collection provides an excellent primer for scholars of methodology.